2007
DOI: 10.1111/j.1439-0434.2007.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

New Pythium Taxa Causing Root Rot on Mediterranean Quercus Species in South‐west Spain and Portugal

Abstract: Pythium spiculum, a recently described new taxon, has been frequently isolated from declining Quercus rotundifolia and Q. suber roots and rhizosphere since 2003 in southern Iberia. In soils of declining Quercus forests this species was found as frequently as Phytophthora cinnamomi which, until now, was the only oomycete described as a Quercus root rot pathogen in the region. Inoculation tests conducted on young Q. rotundifolia plants showed that Py. spiculum is an aggressive root pathogen, although producing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 18 publications
(65 reference statements)
1
83
0
2
Order By: Relevance
“…A number of studies in previously unexplored natural ecosystems have also revealed several undescribed Pythium species (e.g. Nechwatal & Osswald 2003;Paul 2003;Romero et al 2007), as well as oomycetes from the Saprolegniaceae (e.g. Dick 1971).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in previously unexplored natural ecosystems have also revealed several undescribed Pythium species (e.g. Nechwatal & Osswald 2003;Paul 2003;Romero et al 2007), as well as oomycetes from the Saprolegniaceae (e.g. Dick 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, this was obtained by mixing together the same quantity of mycelium from both isolates, to obtain a single suspension of chlamydospores. The inoculum suspension was adjusted to 650 chlamydospores per g of soil (Romero et al 2007). Ten days after soil infestation, each fertilizer was separately added to the soil at 15 mM of Ca 2+ .…”
Section: Soil Experimentsmentioning
confidence: 99%
“…Three open forests were chosen from those previously studied, with known presence of P. cinnamomi infecting oak roots (Romero et al 2007). The fourth site was a recently forested rangeland (10 years-old trees) free of oak root disease.…”
Section: Methodsmentioning
confidence: 99%
“…Trays were incubated in a growth chamber (12 h light per day, 18-24°C), with watering as needed. Twenty five days after inoculation, root symptoms were assessed for each plant on a 0-4 scale, according to the percentage of root necrosis recorded (0=0% necrotic tissue, 1=1-33%, 2=34-66%, 3=67-99%, 4=dead plant) (Romero et al, 2007). ANOVA was performed for emergence and root symptom values, considering the cultivar, the presence of P. cinnamomi in the soil, and their interaction as factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation